Habitat and soil associations of a fossorial toad in a Sonoran Desert riparian forest. (October 2020) - Riddle, Sidney B.; Bateman, Heather L.
Abstract: Despite occupying small land areas, riparian systems provision a large number of vertebrates, including amphibians, one of the most threatened vertebrate taxa. We associated capture rates of a fossorial desert anuran ( Scaphiopus couchii ) to non-native plant invasion and shrub encroachment via soil traits and habitat physiognomy in native, invaded, and shrub-encroached riparian habitats in the Sonoran Desert. We measured habitat and anurans at 18 sites along the San Pedro and Gila Rivers in three stand types based on dominant trees, cottonwood-willow forest ( Populus-Salix ), mesquite woodland ( Prosopis ), and non-native saltcedar stands ( Tamarix ). Dominant tree species were useful descriptors of habitat physiognomy. Spadefoots were associated with xeroriparian habitat at Prosopis sites and nearly absent from Tamarix sites. Soil moisture and texture heavily influenced spadefoot partitioning across forest types. Altering in-stream flow has modified riparian areas by causing xerification, Prosopis expansion, and proliferation of non-native species. The effects of Prosopis encroachment on this fossorial anuran may be less than Tamarix invasion, which could be deleterious to many anurans. We suggest monitoring vulnerable amphibians and conservation measures to preserve native riparian habitat. Highlights: Captures of Couch's spadefoot toad ( Scaphiopus couchii ) greater in xeroriparian (mesquite) than invaded (saltcedar) habitat. Habitat selection of spadefoot is difficult to study because they are fossorial with limited surface activity timed with summer monsoon rains. Tree composition is a useful descriptor of habitat physiognomy in riparian forests. Species-habitat models show mesquite woodlands and water retaining soils are good predictors of spadefoot occurrence. Couch's spadefoot should be added to list of wildlife negatively affected by monotypic stands of invasive saltcedar.